2019
DOI: 10.1007/s00251-019-01130-z
|View full text |Cite
|
Sign up to set email alerts
|

Divergence between genes but limited allelic polymorphism in two MHC class II A genes in Leach’s storm-petrels Oceanodroma leucorhoa

Abstract: The major histocompatibility complex (MHC) is critical to host-pathogen interactions. Class II MHC is a heterodimer, with α and β subunits encoded by different genes. The peptide binding groove is formed by the first domain of both subunits (α 1 and β 1 ), but studies of class II variation or natural selection focus primarily on the β subunit and II B genes. We explored MHC II A in Leach's storm-petrel, a seabird with two expressed, polymorphic II B genes. We found two II A genes, Ocle-DAA and Ocle-DBA, in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Therefore, our finding of one to at least three gene copies of both MHC classes in common buzzards from multiple forms of high-throughput sequencing data was unexpected, and strongly suggests CNV is present in this species. We also found tandem pairs of class IIA and IIB genes in our long-read data, consistent with tandem duplications seen in mammals [ 64 ] and in some non-model bird species [ 65 67 ]. By retrieving sequences from haplotype-aware contig long-read assemblies and blast-searching them against RNAseq transcripts, we were able to confirm that all three loci for each MHC class are expressed (Additional file Table S 4 ).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, our finding of one to at least three gene copies of both MHC classes in common buzzards from multiple forms of high-throughput sequencing data was unexpected, and strongly suggests CNV is present in this species. We also found tandem pairs of class IIA and IIB genes in our long-read data, consistent with tandem duplications seen in mammals [ 64 ] and in some non-model bird species [ 65 67 ]. By retrieving sequences from haplotype-aware contig long-read assemblies and blast-searching them against RNAseq transcripts, we were able to confirm that all three loci for each MHC class are expressed (Additional file Table S 4 ).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, we are aware of only two population-wide screening studies of MHC-IIA genes in birds (chicken and the Leach’s storm-petrel Oceanodroma leucorhoa ), and both showed a low level of polymorphism. Specifically, there were only four nucleotide and one amino acid polymorphisms detected within a single MHC-IIA gene in the chicken ( Salomonsen et al, 2003 ), whereas two IIA genes were found in the storm-petrel: DAA with a single allele and DBA with three alleles differing from each other by single non-synonymous substitutions ( Rand et al, 2019 ). This clearly contrasted with markedly diverged MHC-IIB alleles, as found in the same study ( Rand et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there were only four nucleotide and one amino acid polymorphisms detected within a single MHC-IIA gene in the chicken ( Salomonsen et al, 2003 ), whereas two IIA genes were found in the storm-petrel: DAA with a single allele and DBA with three alleles differing from each other by single non-synonymous substitutions ( Rand et al, 2019 ). This clearly contrasted with markedly diverged MHC-IIB alleles, as found in the same study ( Rand et al, 2019 ). Here, we only examined MHC-IIA sequences from one individual per species, so we had no insight into the intra-specific MHC-IIA variation and we can only discuss polymorphism across species.…”
Section: Discussionmentioning
confidence: 99%
“…Although we acknowledge that the hypothesis on the specialization of gene lineages in terms of antigen recognition is highly speculative, we recommend that it should be put to further investigation at the intra-specific level. So far, we are aware of intra-specific comparisons of selection at both gene lineages only in a single bird species, clearly showing sequence divergence and codon-specific differences in selection signal between the peptide-binding domains of the two gene lineages in the Leach’s storm petrel ( 57 , 58 ). Interestingly, MHC-IIB sequences showed much greater sequence divergence between gene lineages than MHC-IIA and this divergence was found to be primarily driven by positive selection concentrating at the putative peptide-binding sites, suggesting possible functional differences in antigen recognition ( 58 ).…”
Section: Discussionmentioning
confidence: 99%